Internal Migrant versus Non-Migrant Female Worker: The Effect of Family Responsibility on Job Performance in Guangzhou, China - Xiaoyan Yang; Kandappan Balasubramanian; Joaquim Dias Soeiro (Journal of Tourism, Sustainability and Well-being, 2025)
This study explores and compares the impact of family responsibility on job performance among internal migrant and non-migrant female workers. A total of 155 questionnaires were collected from female housekeeping attendants working in hotels in Guangzhou, China. The analysis used partial least squares structural equation modeling (PLS-SEM) and multiple-group analysis. The findings reveal a significant difference in the influence of family responsibility on job performance between the migrant and non-migrant female worker groups. Specifically, the direct effect of family responsibilities on job performance is more pronounced for non-migrant female workers compared to their migrant counterparts. This study underscores the importance of cultivating employees’ awareness of family responsibilities. It contributes substantially to theoretical research by extending our understanding of the relationship between family responsibilities and job performance within the job demands-resources model (JD-R).